Nutrient digestibility and changes in feeding behavior of cattle fed cottonseed and vitamin E - Ricardo Galbiatti Sandoval Nogueira; Flavio Perna Junior; Angélica Simone Cravo Pereira; Paulo Henrique Mazza Rodrigues (Scientia Agricola)
ABSTRACT: High lipid concentration in ruminant diets often harms nutrient digestibility and feed intake; thus, a protected lipid and antioxidant source can be considered as an alternative for improving diet energy without putting animal production at a disadvantage. The aim of this study was to evaluate the dry matter intake (DMI), nutrient digestibility and feeding behavior of cattle fed cottonseed and vitamin E. Six cannulated cows, non-pregnant, non-lactating were distributed in a replicated 3 × 3 Latin Square design. Feed was offered ad libitum twice daily. Treatments were: 1) Control, 2) CS: 30 % cottonseed included; and 3) CSVitE: 30 % cottonseed plus 500 IU VitE included. Data were analyzed by SAS (Statistical Analysis System, v.9.3) and the significance was declared at p < 0.05. Diets with cottonseed had 22 % greater digestibility of ether extract and 9 % lower digestibility of non-fiber-carbohydrates compared to the control. Treatments with cottonseed had 13 % higher time eating, 48 % more ruminating, 34 % more chewing and 17 % lower time idling compared to the control. Molar proportion of propionate was 36 % higher and the butyrate and acetate:propionate ratio were 27 % and 30 % lower, respectively, for the cottonseed treatments compared to the control. Including cottonseed up to 30 % can be used to increase diet energy density leading to improvements in feeding behavior and ruminal parameters. The inclusion of Vitamin E did not result in benefits to cattle when it was combined with cottonseed. Further studies should be undertaken to evaluate vitamin E levels in association with different amounts and lipid sources.